Assessment the bacterial leakage of four endodontic root canal sealers using fresh human saliva, an ex vivo study - Tour Savadkouhi, Sohrab; Roghanizad, Nasrin; Aghabeigi, Mina; Sangchouli, Sima; Khajavi, Faezeh; Khalilak, Zohreh (Iranian Endodontic Journal, 2020)
Introduction: Bacterial leakage has considerable role in endodontic related failures. The aim of this study was to compare the bacterial leakage of bioceramic and resin based root canal sealers. Methods and Materials: Sixty-eight maxillary central incisors were included in this experimental study and randomly allocated to four groups which obturated with GP and four different sealers (AH Plus=15, AdSeal=15, Well Root ST=15, MTA Fillapex=15) and control groups (positive =4, negative =4). A dual chamber technique was carried out using fresh human saliva and traced for 90 days. Chi-square and Long Rank test was performed for data analysis. Results: Bacterial leakage was observed in 33.3% of Well Root ST, 40% of AH Plus, 53.3% of AdSeal and 66.6% of MTA Fillapex group. The difference between Well Root ST and MTA Fillapex groups was significant (P= 0.02). The mean leakage time between Well Root ST (85.6 days) and MTA Fillapex groups (71.2 days) was significant (P= 0.037). Conclusion: Based on the result of this study, bacterial leakage was observed in all experimental groups.Respectively Well Root ST and MTA Fillapex groups showed the least and highest bacterial leakages. Key words: Bacterial leakage, Bioceramic sealer, Canal sealer, Epoxy resins, Root canal filling materials, Saliva